Empowerment of Indonesian Workers Who Will Work Abroad to Support Economic Resilience: A Case Study of East Java Province - Tatar Bonar Silitonga; I Wayan Midhio; M. Adnan Madjid (International Journal of Science and Society, 2020)
This study aims to analyze the implementation of empowerment carried out for prospective migrant workers who will work abroad in order to support economic security. This research was conducted in Malang and Blitar districts in East Java Province using a qualitative approach. Data collection through interviews, document studies, and focus group discussions (FGD). The findings of this study are, first, the factors underlying migrant workers working abroad on the basis of their own initiative, economic drive, level of education, market demand, and psychosocial factors. Second, the benefits of the existence of migrant workers for local residents from migrant workers are as economic drivers and the development of the character of the community work ethic. Third, the problems most felt by migrant workers and their families include aspects of the lack of certainty in the time of departure, work and treatment that is not in accordance with the work contract, bear the family's longing, as well as the prejudice and potential divorce after returning to the homeland. Fourth, the implementation of pre-placement, placement, and post-placement of migrant workers working abroad that involves the role of government, companies, users / agents of partners, but in its implementation is still not optimal. Fifth, the implementation of the preparation of migrant workers to work abroad has positive implications in the form of protection of the rights and readiness of migrant workers to carry out work activities abroad, but on the other hand also has negative implications because the empowerment of the government is still not optimal can disrupt the process of support for efforts to achieve economic security.